IN SILICO ANALYSIS OF XANTHINE OXIDASE INHIBITOR OF ETHYL ACETATE FRACTION OF ETHANOLIC EXTRACT OF STELECHOCARPUS BURAHOL (BL.) HOOK F. AND TH. LEAVES - Diniatik; Pramono, Suwijiyo; Riyanto, Sugeng (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The research was conducted by in silico analysis of xanthine oxidase inhibitors of volatile compounds from ethyl acetate fraction of ethanolic extract of Stelechocarpus burahol (Bl.) Hook f. and Th. leaves. The objective of the research was to determine the active compounds as a potential inhibitor of xanthine oxidase by using in silico screening method. Methods: The research was conducted using volatile compounds that were obtained by using gas chromatography of ethyl acetate fraction of ethanolic extract of S. burahol leaves and models of xanthine oxidase inhibitor downloaded via Protein Data Bank (PDB) with code 3BDJ, then performed docking process using the PyRx program, and then evaluated of the free energy (Î”G) as docking process results. Results: Volatile compounds in the ethyl acetate fraction of ethanolic extract were 3 heptene, 2,2,4,6,6-pentamethyl (2.15%),Â  methyl hexadecanoate (4.16%), ethyl tridecanoate (34.63%), methyl octadecanoate (7.26%), ethyl hexadecanoate (51.8%). The result showed that three of the chemical compounds have the lower free energy value as xanthine oxidase inhibitors than oxypurinol. Conclusion: They were ethyl tridecanoate, methyl octadecanoate, ethyl hexadecanoate with free energy (Î”G) -10.7, -7.6, -7.1 kcal / mol.Â 